The role of rural tourism in sustainable rural development using the example of Kashubia (Geography and Tourism, 2023)
The Kashubia region is characterized by its rich history and unique folklore, beautiful landscape, natural wealth, clean lakes and magnificent beaches of the Polish coast. Kashubia is also known for its unique language, cuisine, historical sites and music and art. It is undoubtedly, one of the most beautiful corners of Poland. The purpose of the study was to present and characterize the role of rural tourism in the sustainable development of rural areas and to assess the degree of its development in a sustainable direction. The study showed the forms and types of rural tourism and its functions. An important element of the study was the evaluation of tourism development, including accommodation and accompanying facilities in accordance with the concept of green economy, which has a special role in the development of rural areas, due to the fact that it is based on natural resources. The spatial scope concerns the area of historic Kashubia within the administrative boundaries of the three counties of Pomorskie Voivodeship (i.e., Koscierzyna, Chojnice and Kashubia counties). The paper uses a spatial analysis based on data from the Central Statistical Office (CSO) and a survey conducted in 2021-2023. The results of the study clearly indicate that there has been significant progress in the development of tourism infrastructure during the period under review. Rural tourism can contribute to the development of sustainable rural areas of Kashubia, in line with the current of the green economy concept. Of particular importance is folklore and folk art, including folklore events; harvest festivals, festivals, folk concerts and the activities of agrotourism farms, which combine the tradition of the farming profession with environmental protection and promotion of the Kashubian region.